Efecto jurídicos de la falta de contradicción en los sumarios administrativos iniciados contra docentes del Colegio Dr. Juan Henríque Coello del cantón Machala periodo lectivo 2011-2012. - Luzuriaga Salazar, Wilson David (2014)
Due process and the principle of contradiction argue for the thematic development for justice operators consider their applicability not mechanically but in the exercise of constitutional rights and guarantees, so that the two teachers summarily fully exercise their rights.